TINJAUAN YURIDIS TENTANG KEPASTIAN HUKUM TERHADAP TENAGA KESEHATAN TRADISIONAL AKUPUNKTUR DI NEGARA INDONESIA - Tan, Suminah; Sinaga, Wetmen (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Indonesia as a constitutional state, have legal rules to guarantee and protect the rights of its citizens. Health is important element in Indonesia’s development. Health workers who provide health services to the community, are citizens who have the same rights to realize the welfare of society. In health services, traditional health workers are one of the health workers as stipulated in law number 36 of 2009 concerning health. Traditional health workers divided into skilled health workers and health workerswho use potions as stipulated in law number 36 of 2014 concerning health workers. Of the various rules that have been set by the government, these rules regulate policies regarding health services, helath workers and users of helath services. The rules made are intended for health services, in order to obtain services that have fair legal certainty, both for health workers and for patients. Fair rules as positive law provide legal certainty and do not raise doubt in terms of helath services.